Evaluating the factors influencing on Customer Retention in the Mobile Telecommunication Industry in Colombo District of Sri Lanka - Karunakaran, A.S.J.; Selvarajan, P. (Sabaragamuwa University of Sri Lanka, 2016)
The aim of this research study is to evaluate the factors influencing the customer retention in the mobile telecommunication industry in Colombo district of Sri Lanka. This study adds many other supporting materials especially for the literature review. Moreover, the conceptual model used in this study also supports to find the influence of the factors on customer retention. An in-depth interview and a questionnaire survey have been done by the researchers ingus100 retained customers. The data were collected from the customers in Colombo who have obtained 10 years services with the same telecommunication company, based on the convenience sampling method. The data is analyzed through regression analysis with the help of the SPSS version 16.0. Out of four variables, it is found that service quality, payment equity and effective commitment have the influence on the customer retention. However, the fourth variable-loyalty program has no significant influence on the customer retention. The findings can help the service providers to identify the impact of loyalty program, service quality, payment equity and effective commitment toward the customer retention. This current study has its own limitation since this research is only conducted in Colombo district. Therefore, future studies can be extended to other districts in Sri Lanka with a large sample.
Keywords: Customer retention; Effective commitment; Payment equity; Service quality; Telecommunication industry